PENGARUH USIA TERHADAP KESEIMBANGAN KEHIDUPAN KERJA YANG DIMEDIASI OLEH BATASAN PEKERJAAN DI KANTOR DAN BATASAN PEKERJAAN DI RUMAH PADA KARYAWAN SEKTOR PERBANKAN DI BANDA ACEH - Maulidia Maulidia; Fairuzzabadi Fairuzzabadi (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2021)
This study aims to measure the effect of Age on the Opportunity of Work Life which is mediated by Work Limits at the Office and Work Limits at Home for Banking Sector Employees in Banda Aceh. The sample used in this study were employees of the Banking Sector in Banda Aceh which had 118 respondents. The data equipment used in this study was a questionnaire. The sampling technique used is Probability Sampling. Causal steps is used as a method of analysis to see the effect of all the variables involved.Based on the results of the Causal Step analysis, that affects Work-Life Balance, Age has a positive effect on Work Limits at the office, Age has a positive effect on Work Limits at home, Work Limits at the office have an effect on Work Balance, Work Limits at home have a positive effect on Work-Life Balance, Age positive effect on work-life balance mediated by work limitations at the office and work limits at home, work limitations at the office and work boundaries at home is positive and a direct relationship to work-life balance.